2008
DOI: 10.1590/s1516-31802008000200008
|View full text |Cite
|
Sign up to set email alerts
|

Tepid sponging plus dipyrone versus dipyrone alone for reducing body temperature in febrile children

Abstract: CONCLUSIONS:Tepid sponging plus dipyrone cooled faster during the fi rst 15 minutes, but dipyrone alone presented better fever control over the two-hour period. Tepid sponging caused mild discomfort, crying and irritability for most of the children.KEY WORDS: Fever. Dipyrone. Child. Baths. Antipyretics. CLINICAL TRIAL REGISTRATION NUMBER:ACTRN12608000083392. 108Sao Paulo Med J. 2008;126(2):107-11.during the previous six hours were excluded, as were children with known liver or renal diseases, gastrointestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
23

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 15 publications
2
28
0
23
Order By: Relevance
“…After removal of duplicates, 1286 studies remained; 2 systematic reviews (Meremikwu & Oyo‐Ita, , ) and 14 experimental studies were selected according to the inclusion/exclusion criteria. Finally, 14 experimental studies (Agbolosu et al, ; Aksoylar et al, ; Alves et al, ; Brandts, ; Friedman & Barton, ; Hunter, ; Kang et al, ; Kinmonth, ; Lee et al, ; Mahar et al, ; Newman, ; Sharber et al, ; Steele, Tanaka, Lara, & Bass, ; Thomas et al, ) were included (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After removal of duplicates, 1286 studies remained; 2 systematic reviews (Meremikwu & Oyo‐Ita, , ) and 14 experimental studies were selected according to the inclusion/exclusion criteria. Finally, 14 experimental studies (Agbolosu et al, ; Aksoylar et al, ; Alves et al, ; Brandts, ; Friedman & Barton, ; Hunter, ; Kang et al, ; Kinmonth, ; Lee et al, ; Mahar et al, ; Newman, ; Sharber et al, ; Steele, Tanaka, Lara, & Bass, ; Thomas et al, ) were included (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The general characteristics of the 14 selected studies ( n = 1234) are shown in Table . While 3 studies (Alves et al, ; Lee et al, ; Thomas et al, ) were published since 2000, most studies were published before 2000 (Agbolosu et al, ; Aksoylar et al, ; Brandts, Ndjave, Grainger, & Kremsner, ; Friedman & Barton, ; Hunter, ; Kang et al, ; Kinmonth, Fulton, & Campbell, ; Mahar, 1994; Newman, ; Sharber, ; Steele et al, ). While 2 studies were conducted in the United States (Friedman & Barton, ; Sharber, ), 2 studies (Kang et al, ; Lee et al, ) were conducted in the Republic of Korea; a single study was conducted in Australia, Brazil, Canada, Gabon, Hawaii, India, Malawi, Thailand, Turkey, and the United Kingdom (Agbolosu et al, ; Aksoylar et al, ; Alves et al, ; Brandts et al, ; Hunter, ; Kinmonth et al, ; Mahar, 1994; Newman, ; Steele et al, ; Thomas et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kompres tepid sponge adalah sebuah teknik kompres hangat yang menggabungkan teknik kompres blok pada pembuluh darah supervisial dengan teknik seka [6].…”
Section: Tinjauan Pustakaunclassified
“…crying and irritability were observed respectively in 52 % and 36 % of the sponged children and in none and only two of the controls. the authors concluded that tepid sponging plus metamizole cooled faster during the first 15 min, but metamizole alone presented better fever control over the two-hour period (4). only a few controlled clinical trials have compared metamizole with other analgesics in children.…”
Section: Overview Of Efficacymentioning
confidence: 99%